2023
DOI: 10.1002/adfm.202210805
|View full text |Cite
|
Sign up to set email alerts
|

Latch Applicator for Efficient Delivery of Dissolving Microneedles Based on Rapid Release of Elastic Strain Energy by Thumb Force

Abstract: Dissolving microneedle (DMN) is an attractive alternative to parenteral and enteral drug administration owing to its painless self‐administration and safety due to non‐generation of medical waste. For reproducible and efficient DMN administration, various DMN application methods, such as weights, springs, and electromagnetic devices, have been studied. However, these applicators have complex structures that are complicated to use and high production costs. In this study, a latch applicator that consists of onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…32 For efficient insertion of the EMN, we used a homemade latch applicator that can achieve the optimum pressing force and impact velocity using only the thumb force. 33 In the next section, we described the formulation screening results of the yolk layer for maintaining the activity of the influenza vaccine mounted on the EMN that is critical for the successful vaccination.…”
Section: Resultsmentioning
confidence: 99%
“…32 For efficient insertion of the EMN, we used a homemade latch applicator that can achieve the optimum pressing force and impact velocity using only the thumb force. 33 In the next section, we described the formulation screening results of the yolk layer for maintaining the activity of the influenza vaccine mounted on the EMN that is critical for the successful vaccination.…”
Section: Resultsmentioning
confidence: 99%
“…Concerning the misalignment and distortion of character patterns, the slipping of MAPs or skin, which may occur during application, contributes to the misalignment of patterns, including tilted, moved, distorted, or stretched patterns. We considered that a xing device, such as an applicator 32 , can be helpful to x the MAP or skin stably during its application, resulting in patterns without any shape deformations.…”
Section: Resultsmentioning
confidence: 99%
“…Clinically, dissolving MNs would be applied to the skin using an applicator to improve skin puncturability [ 50 , 51 ]. Recently, we observed that needles with a small base diameter broke near the base without bending tips during skin insertion, which was confirmed by micro-CT imaging.…”
Section: Discussionmentioning
confidence: 99%